2022
DOI: 10.1002/bio.4189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentration and shell thickness on the optical behavior of aqueous CdTe/ZnSe core/shell quantum dots (QDs) exposed to ionizing radiation

Abstract: In this work CdTe/ZnSe core/shell quantum dots (QDs) were synthesized via a simple, rapid and room temperature photochemical approach. Optical properties of aqueous prepared CdTe/ZnSe QDs were studied systematically under gamma irradiation with dose range of 0 Gy to 20 kGy. The obtained results showed a regular red shift behavior versus gamma irradiation dose, in photoluminescence peak and absorption edge of the CdTe/ZnSe QDs. Structural properties of CdTe/ZnSe QDs before and after gamma irradiation were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recently, semiconductor quantum dots (QDs) have been widely employed in various underdevelopment technologies such as light-emitting diodes (LEDs), ultrafast lasers, solar cells, and environmental sensors due to their unique optical properties. [1][2][3][4][5][6] Compared to the bulk semiconductors, QDs indicate interesting electronic and optical properties because of the quantum confinement effects. [7] CdTe is one of the famous II-VI semiconductors in which its QDs are widely used in different new technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, semiconductor quantum dots (QDs) have been widely employed in various underdevelopment technologies such as light-emitting diodes (LEDs), ultrafast lasers, solar cells, and environmental sensors due to their unique optical properties. [1][2][3][4][5][6] Compared to the bulk semiconductors, QDs indicate interesting electronic and optical properties because of the quantum confinement effects. [7] CdTe is one of the famous II-VI semiconductors in which its QDs are widely used in different new technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum dots (QDs) have emerged as highly promising colloidal nanomaterials for fluorescence sensing due to their optical stability with a wide absorption spectrum, high quantum yields, excellent photostability, and narrow emission spectrum. , Therefore, QDs showed potential in ionization radiation sensing; however, the results have been inconclusive. For example, Zanazzi et al found a decrease in the fluorescence intensity of colloidal InGaP/ZnS QDs embedded in polydimethylsiloxane under 2 MeV proton irradiation . Similarly, Stodilka et al observed the optical degradation of CdSe/ZnS QDs upon gamma-ray irradiation.…”
Section: Introductionmentioning
confidence: 99%